2021
DOI: 10.1177/0020720920983704
|View full text |Cite
|
Sign up to set email alerts
|

Research on online management system of network ideological and political education of college students

Abstract: With the development of the network society, the life of college students is shrouded by the network society, and there are more and more channels for them to contact various kinds of information, which brings new challenges to their ideological and ideological behaviors. We need to use the correct, active, positive way to increase the ideological network political education of students. College students' ideological and political education also gradually stepped into the network education wave, in the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Li, K. et al developed a college ideological and political online education management system based on cloud computing technology, relying on which students' ideological patterns can be better corrected, students' behaviors are truly student-centered, and students' teaching is truly student-centered. Behavior, truly student-centered teaching, effectively enhances the quality of physical and mental development of college students for the innovative development of ideological and political education in colleges and universities to provide a new reference [14]. Su, R. based on the Java E. E. framework to establish the evaluation model of ideological and political education in colleges and universities, ideological and political education and the combination of network platforms can help students more easily access diversified ideological and political education resources so that the ideological and political education in colleges and universities can really realize the quality of collaborative parenting.…”
Section: Review Of the Current State Of Researchmentioning
confidence: 99%
“…Li, K. et al developed a college ideological and political online education management system based on cloud computing technology, relying on which students' ideological patterns can be better corrected, students' behaviors are truly student-centered, and students' teaching is truly student-centered. Behavior, truly student-centered teaching, effectively enhances the quality of physical and mental development of college students for the innovative development of ideological and political education in colleges and universities to provide a new reference [14]. Su, R. based on the Java E. E. framework to establish the evaluation model of ideological and political education in colleges and universities, ideological and political education and the combination of network platforms can help students more easily access diversified ideological and political education resources so that the ideological and political education in colleges and universities can really realize the quality of collaborative parenting.…”
Section: Review Of the Current State Of Researchmentioning
confidence: 99%
“…The results showed that in learning management for junior high schools it is necessary to apply a learning process that can arouse students' enthusiasm. [11] Said that with the development of a network society, student life was enveloped by a network society. Then [12] said that the challenge in facing difficulties in involving students was to raise students' enthusiasm.…”
Section: ) Provide Social Support To Students To Be Able To Complete Their Schoolworkmentioning
confidence: 99%
“…It aids college students to update their political wisdom very quickly, learn from rich and diverse resources, and gain the corresponding course information. Through Internet political learning, college students get well-equipped [6]. The technology has emerged with increasing mutual assistance of college students and the Internet, in the form of online learning.…”
Section: Introductionmentioning
confidence: 99%